2006
DOI: 10.1177/001440290607200402
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Access: The Disproportionality of African American Students with Disabilities across Educational Environments

Abstract: This study investigated the extent to which the overrepresentation of African American students in more restrictive special education settings is attributable to their overrepresentation in disability categories more likely to be served in more restrictive educational environments. Within 5 disability categories (emotional disturbance, mild mental retardation, moderate mental retardation, learning disabilities, and speech and language), African American students were overrepresented in more restrictive educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(139 citation statements)
references
References 27 publications
5
131
1
2
Order By: Relevance
“…Elas têm o infortúnio de serem educadas em classes de Educação Especial, onde as experiências acadêmicas não são comparáveis àquelas de seus colegas que estão em salas de aula regulares. Considerando que, tradicionalmente, têm sido negadas aos afroamericanos as oportunidades de se sobressair na sociedade estadunidense, sua seleção abusiva para serviços de Educação Especial parece ser a continuação da prática de tratá-los como inatamente inferiores (CONAHAN, 2003 (SKIBA, 2006). Dezesseis por cento da população da escola pública, os estudantes afroamericanos constituem 27% dos estudantes classi cados como mentalmente retardados treináveis e seriamente perturbados emocionalmente (HARRIS, 2004).…”
Section: Monitoramento De Habilidadesunclassified
“…Elas têm o infortúnio de serem educadas em classes de Educação Especial, onde as experiências acadêmicas não são comparáveis àquelas de seus colegas que estão em salas de aula regulares. Considerando que, tradicionalmente, têm sido negadas aos afroamericanos as oportunidades de se sobressair na sociedade estadunidense, sua seleção abusiva para serviços de Educação Especial parece ser a continuação da prática de tratá-los como inatamente inferiores (CONAHAN, 2003 (SKIBA, 2006). Dezesseis por cento da população da escola pública, os estudantes afroamericanos constituem 27% dos estudantes classi cados como mentalmente retardados treináveis e seriamente perturbados emocionalmente (HARRIS, 2004).…”
Section: Monitoramento De Habilidadesunclassified
“…These discrepancies are quite disturbing, especially with regard to the quest to offer all students the opportunity for upward social mobility. Such disproportionate group membership can be traced to many other areas of the education and criminal justice systems in the United States (McKenna, 2013;Skiba, Poloni-Staudinger, Gallini, Simmons, Feggins-Azziz, 2006;Zhang, Katsiyannis, Ju, & Roberts, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Black students, in general, are underserved academically (Darling-Hammond, 2000;Townsend, 2002) and overrepresented in special education (Donovan & Cross, 2002). Black students with disabilities are further overrepresented in more restrictive educational environments (Skiba, Poloni-Staudinger, Gallini, Simmons & Feggins-Azziz, 2006). In other words, even within special education, Black students with disabilities are more likely to be served in separate settings.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…The concern with placing Black students with disabilities in more restrictive, segregated settings instead of more inclusive, general education classrooms is often cited by researchers. Black students with disabilities are more likely to be underrepresented in general education settings and overrepresented in more restrictive settings (Blanchett, 2009;Skiba et al, 2006), regardless of gender or type of disability (LeRoy & Kulik, 2001). The U.S. Department of Education (2005) revealed that only 38.6% of black students with disabilities spent most of their school day in the regular classroom in comparison to 54.7% of White students.…”
Section: Black Students In Urban Special Educationmentioning
confidence: 99%
See 1 more Smart Citation